Altered sterol profile induced in Leishmania amazonensis by a natural dihydroxymethoxylated chalcone - Torres-Santos, Eduardo Caio (Oxford University Press, 2009)
OBJECTIVES: The effects of the antileishmanial chalcone 2′,6′-dihydroxy-4′-methoxychalcone (DMC) on Leishmania amazonensis sterol composition and biosynthesis were investigated to obtain information about the mechanism of growth inhibition by DMC on this parasite. METHODS: The interference of sterol biosynthesis by DMC was studied in drug-treated promastigotes by two different methods. (i) Newly synthesized sterols from parasites grown in the presence of [(3)H]mevalonate were analysed by thin layer chromatography (TLC)/fluorography. (ii) Total sterols extracted from the parasites grown with or without DMC were characterized by gas chromatography coupled to mass spectroscopy (GC/MS). RESULTS: TLC and GC/MS analyses of sterols extracted from DMC-treated promastigotes revealed the accumulation of early precursors and a reduction in the levels of C-14 demethylated and C-24 alkylated sterols, as well as a reduction in exogenous cholesterol uptake. CONCLUSIONS: This study demonstrates that the natural chalcone DMC alters the sterol composition of L. amazonensis and suggests that the parasite target is different from other known sterol inhibitors.